Improved protocol for the isolation of naïve follicular dendritic cells - Sato, Kazuki; Honda, Shin-ichiro; Shibuya, Akira; Shibuya, Kazuko (Molecular immunology, 2016)
•CD45−ICAM-1+CD21/35+ cells were isolated from naïve mouse spleen by flow cytometry.•CD45−ICAM-1+CD21/35+ cells expressed characteristic FDC markers.•CD45−ICAM-1+CD21/35+ cells retained and presented antigen.•CD45−ICAM-1+CD21/35+ cells were defined as a highly enriched FDC population. Follicular dendritic cells (FDCs) in lymphoid organs play an important role in the humoral immune response. However, because the isolation of FDCs is difficult due to their very small population size and fragility under mechanical and chemical stresses, the genetic and biochemical characteristics of FDCs remain unclear. Previously, we identified FDCs as ICAM-1+ cells in the CD45− non-hematopoietic cell fraction from naïve mouse spleen after cell separation by means of digestion with a combination of enzymes. In the present study, using a new combination of enzymes, we found that FDCs are highly enriched in the CD45−ICAM-1+CD21/35+ cell fraction. CD45−ICAM-1+CD21/35+ cells in the mouse spleen retained an antigen administered in vivo for more than 7 days. Moreover, CD45−ICAM-1+CD21/35+ cells isolated from the spleen of mice administered with a cognate antigen enhanced the survival and proliferation of antigen-specific B cells in vitro. Our improved protocol for the isolation of naïve FDCs will be useful for the analysis of FDCs in vitro and in vivo.